Evaluasi Kebijakan Reklamasi Pantai Marina di Kota Semarang - Ricky Wismoyo; Purwoko .; Nunik Retno (Journal of Politic and Government Studies, 2016)
Semarang city having broad areas 373,70 kilometers2 .With long coastlinewhich reached 13.6 kilometers, Therefore coastal areas in the city ofsemarang very has the potential to areas in additional or reclaimed that indoing in marina beach .In accordance with regional regulation which prevailat that number 8 years 2004 about layout of semarang city , marina area thatwill be reclaimed are allocated for the area building that support functionhousing .To education for example , sports , health and recreation .So , aimedas the area that support the common interests .The purpose of this research is to give evaluation or an assessment of policythe purpose of reclaiming the marina beach which accounted for target , aperiod of time the implementation of the , a budget and assessing how outputand outcome of these policies reclaiming the extent that was already carriedout .This research writer do research evaluation with the qualitative method. Thedata collected directly from the or source that deals with this research,obtained through direct interview with respondents.The interviewsconducted with a decisive manner of key person. Informants selected canprovide information that is relevant by research this is the associated withthe policy of reklamsi the coast of semarang, among others of bapeda,environmental board, of the city of semarang agency, works agency umun orbina marga, department of water resources management, among collegecompetent and community figures.Based on the research done reclamation are believed to have match to be thesolution the availability of land occupancy .This is supported to the city2semarang having long coastlines reached 13.6 kilometers , therefore coastalareas within the city of semarang potential to addition areas or reclaimed .Recommendations policy the planned reclamation, marina this is still feasibleto continue with a need of a revision of agreement policy itself , as a period oftime the implementation of the 75 year , and area on the agreement of 200ha ,or result reclamation , should be used for development tourism , industry andpublic facilities as the residential focus in the the city of semarang still asparse population .Keywords: evaluation , policy , reclamation